2013
DOI: 10.1098/rstb.2012.0479
|View full text |Cite
|
Sign up to set email alerts
|

A greener Greenland? Climatic potential and long-term constraints on future expansions of trees and shrubs

Abstract: Warming-induced expansion of trees and shrubs into tundra vegetation will strongly impact Arctic ecosystems. Today, a small subset of the boreal woody flora found during certain Plio-Pleistocene warm periods inhabits Greenland. Whether the twenty-first century warming will induce a re-colonization of a rich woody flora depends on the roles of climate and migration limitations in shaping species ranges. Using potential treeline and climatic niche modelling, we project shifts in areas climatically suitable for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 73 publications
2
71
2
Order By: Relevance
“…While phenologies of eelgrass and brent geese do not suggest that the birds currently introduce eelgrass seeds from Europe or USA (Clausen et al, 2002), they may contribute to dispersal along Greenland's coast. Research on arctic terrestrial vegetation has shown that Greenland's terrestrial woody flora has a great potential for future expansion but is strongly dispersal limited, with a potentially important role of unintentional introductions (Normand et al, 2013 -Jensen et al, 2012;Clausen et al, 2014;Olesen et al, 2014). Initial signs of positive responses of the vegetation to arctic warming and longer ice-free periods have also been reported (Weslawski et al, 2010;Kortsch et al, 2012;Krause-Jensen et al, 2012).…”
Section: Forecasting Future Coastal Ecosystems In a Warmer Arctic: Tomentioning
confidence: 91%
See 1 more Smart Citation
“…While phenologies of eelgrass and brent geese do not suggest that the birds currently introduce eelgrass seeds from Europe or USA (Clausen et al, 2002), they may contribute to dispersal along Greenland's coast. Research on arctic terrestrial vegetation has shown that Greenland's terrestrial woody flora has a great potential for future expansion but is strongly dispersal limited, with a potentially important role of unintentional introductions (Normand et al, 2013 -Jensen et al, 2012;Clausen et al, 2014;Olesen et al, 2014). Initial signs of positive responses of the vegetation to arctic warming and longer ice-free periods have also been reported (Weslawski et al, 2010;Kortsch et al, 2012;Krause-Jensen et al, 2012).…”
Section: Forecasting Future Coastal Ecosystems In a Warmer Arctic: Tomentioning
confidence: 91%
“…Late August is close to the end of the growing season at 64 • N, suggesting that eelgrass may be unable to complete its life cycle further north at present even though it can sustain dense populations with biomass comparable to that developed further south . Angiosperms have the capacity to complete their life cycle even in N. Greenland far beyond the Arctic Circle (Normand et al, 2013), so there is, in principle, no reason to believe that the photoperiod is an impediment for eelgrass, which has also been reported to cope well with temperatures near freezing point (McRoy, 1969), to do so as well. Flowering and seed production respond to warming in arctic land plants, which have been reported to advance and shorten the flowering period in recent warmer years with less snow cover .…”
Section: Macrophyte-dominated Ecosystems In a Warmer Arcticmentioning
confidence: 99%
“…Range shifts have already been observed among arctic terrestrial species (Serreze et al 2000, Post et al 2009), although recent studies indicate that the current northern distribution limit in Greenland is strongly shaped by dispersal limitation and other disequilibrium dynamics (e.g. unsuitable soil), resulting in migration lags of 100s to 1000s of years (Normand et al 2013). The floating reproductive shoots of eelgrass are capable of long-distance dispersal in marine systems (up to 150 km; Kendrick et al 2012), 117 Fig.…”
Section: Greenland Eelgrass In a Warmer Futurementioning
confidence: 99%
“…Greenland is therefore a suitable study system for quantifying the potential for colonization rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120477 by non-native shrub and tree species as well as their migrational lags. Normand et al [60] in this issue address this problem by applying both a physiologically based tree line model and species distribution models of an array of shrub and tree species currently found in Greenland or occurring elsewhere in high-latitude regions. Using both palaeoclimatic data from different periods back to the Last Glacial Maximum and data deriving from climate change projections, Normand et al [60] conclude that the envelope of suitable climatic conditions for many of these species has existed in Greenland for several thousand years, despite their lack of establishment.…”
Section: Long-term Vegetation Dynamics and Ecosystem Functionmentioning
confidence: 99%